A mixed method evaluation of adult tier 2 lifestyle weight management service provision across a county in Northern England. Issue 3 (24th April 2018) - Ells, L.; Watson, P.; Carlebach, S.; O'Malley, C.; Jones, D.; Machaira, T.; Whittaker, V.; Clements, H.; Walker, P.; Needham, K.; Summerbell, C.; Coulton, V.; et al.
Summary: Adult obesity in the UK remains a public health priority. Current guidance recommends local areas provide multicomponent interventions to treat adults with overweight and obesity; however, there is currently a dearth of published evidence on the evaluation of these programmes. This study reports on a mixed method evaluation of seven tier 2 weight management programmes funded by a local authority in the North of England through their public health grant (a lifestyle multicomponent weight management programme for the treatment of adults with overweight and obesity, but not severe obesity, or obesity with severe co‐morbidities). Data collected from over 2000 participants demonstrated that the proportion of participants achieving 5% initial body weight loss was comparable to that reported in recent UK weight management trials. Two services exceeded national criteria of 30% of participants achieving 5% initial body weight loss at 12 weeks, although long term data was limited. Greater weight loss was also observed in participants aged 35–44 and those without co‐morbidities. This study provides important learning points for improvements in real world weight management services, these include: standardised data collection and management tools; staff training and communication requirements; the importance of programmes that are joined up to wider support services; and the importance of providing ongoing peer and provider support, continuous monitoring and feedback, and physical activities tailored to user needs.